2018
DOI: 10.1093/fampra/cmy028
|View full text |Cite
|
Sign up to set email alerts
|

Perceived cardiovascular risk and attitude towards lifestyle change

Abstract: Perceived cardiovascular risk and incorrect optimism about this hazard have minimal, if any, influence on attitude towards lifestyle change. Patients' motivation seems not to be primarily health related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…While our sample, on average, perceived themselves to be highly susceptible, this perception was not associated with healthier lifestyle intentions. This is in line with a study by Vörös et al ( 2018 ), who neither found a link between patient's estimations of their own cardiovascular risk and their willingness to change their lifestyle. According to the Health Belief Model (HBM) theory, the likelihood of engaging in health-protective behaviors is explained by both the perceived threat of a disease as well as perceptions regarding the effectiveness of behaviors adopted to counteract that threat (Becker, 1974 ).…”
Section: Discussionsupporting
confidence: 93%
“…While our sample, on average, perceived themselves to be highly susceptible, this perception was not associated with healthier lifestyle intentions. This is in line with a study by Vörös et al ( 2018 ), who neither found a link between patient's estimations of their own cardiovascular risk and their willingness to change their lifestyle. According to the Health Belief Model (HBM) theory, the likelihood of engaging in health-protective behaviors is explained by both the perceived threat of a disease as well as perceptions regarding the effectiveness of behaviors adopted to counteract that threat (Becker, 1974 ).…”
Section: Discussionsupporting
confidence: 93%
“…[29][30][31][32] Studies have consistently reported that hypertensive patients often have inaccurate subjective risk perceptions of adverse CVD event 33,34 and underestimate their risk when compared to objective measures such as the FRS. [35][36][37] For example, despite an increased risk of CVD events from comorbidities such as diabetes and unhealthy lifestyle behaviors (smoking), hypertensive patients were unable to provide an accurate risk estimate 33,38,39 even in high-income countries (HICs) such as the Netherlands, 33 US, 40 and Switzerland. 41 Research on CVD risk perceptions in Africa is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Reported examples of barriers to drug adherence are side effects, the complexity of drug regimens and the impact of medication on daily life ( AlGhurair et al., 2012 ). Barriers to performing lifestyle changes could be an underestimation of one's own cardiovascular risk ( Vörös et al., 2018 ). Several interventions have been tried out to help people to adhere to medication by increasing patients’ knowledge ( Gwadry-Sridhar et al., 2013 ), home BP monitoring ( Fletcher et al., 2015 ; Stergiou et al., 2014 ), education on hypertension and advice on lifestyle ( Cheema et al., 2014 ), e-counselling programs ( Nolan et al., 2014 ), other digital interventions ( McLean et al., 2016 ) and linking adherence behaviour with habits, giving adherence feedback to patients, using dose dispenser or other special packaging and motivational interviewing ( Conn et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%